Aproveitamento da casca de banana na elaboração de barras de cereais: avaliação dos compostos bioativos, características físicas e sensoriais - Carvalho, Vania Silva [UNESP] (2015)
The banana peel is an agro-industrial residue, rich regarding to nutritive value and with potential to be used in the development of a new product. In this way, the objective of this work was to study the effect of addition of the banana peel flour in production of cereal bars. The mixture modeling methodology was used to investigate the effects of banana peel flour, rice flakes and oat flour on the sensory acceptability and physical characteristics of the cereal bars; the most and least accepted formulations had their sensory profiles evaluated through descriptive analysis; and the storage of the cereal bars was studied regarding to bioactive compounds and texture properties. Equivalent proportions of three components and binary mixtures of banana peel flour and rice flakes resulted in bars with liking degree in the region of higher response in the triangular diagrams. Yet, the interaction between banana peel flour with rice flakes or oat flour promoted changes to the color, specific volume and adhesiveness of the cereal bars. The external preference mapping showed that cereal bar with 50% of banana peel flour and 50% of rice flakes and the cereal bar with 17% of banana peel flour /66% of rice flakes/17% of oat flour were characterized by the acceptability by appearance, texture, flavor and overall acceptability, as well as greater specific volume, force of rupture and hardness; the formulation with equal proportions of the three ingredients was characterized by acceptability by the aroma, and low intensities of red, yellow and chroma. The addition of banana peel flour also changed the intensity of descriptive terms of the cereal bars, resulting in different sensory profiles in relation to the commercial bar. Cereal bars with higher quantities of banana peel flour were characterized by dark color, banana aroma and bitter taste, while cereal bar with lowest quantity of banana peel flour was characterized by amount of rice flakes and ...